The Urgency and Mechanism of Asset Return for Corruption Crimes - Adhalia Septia Saputri (Ridwan Institute, 2023)
Typicality in Article 2 and Article 3 of Law No. 31 of 1999 jo Law No. 20 of 2001 concerning the Eradication of Corruption Criminal Acts (Tipikor Law) is the existence of elements of state financial losses, the Tipikor Law regulates mechanisms or procedures that can be applied in the form of asset returns through criminal channels, and asset returns through civil channels. The return of Tipikor's assets through civil channels is contained in the provisions in Article 32 paragraph (1), Article 34, Article 38B paragraph (2) and (3) of the Tipikor Law. Return of assets from the criminal route is carried out through a trial process where the judge in addition to imposing the principal crime can also impose additional crimes, the return of assets through this criminal procedure can be, (1) Seizure of tangible or intangible movable property, (2) Payment of substitute money, (3) Criminal fines, (4) Determination of confiscation of goods that have been confiscated, (5) Verdict of confiscation of property for the state. This study aims to know, analyze and answer problems regarding the regulation of the return of assets resulting from corruption in positive law, know, analyze and answer the problem of obstacles in the implementation of the return of assets resulting from this criminal act of corruption, and know, analyze and answer problems about the urgency and mechanism of returning assets resulting from corruption in ius constituendum. The Usefulness of Research on the Urgency and Mechanism of Return of Assets Resulting from Criminal Acts of Corruption.